Improving the lawmaking activities of executive authorities - Akhmetova, N.S.; Birmanova, A.I. (Bulletin of the Karaganda University “Law Series”, 2023)
Lawmaking is the most important function of the executive authorities, through which their activity is manifested, aimed at the qualitative development of Kazakh society and the performance of all other functions of the state. The article examines the features of subordinate lawmaking, which are due to the multiplicity of the system of executive authorities. It is noted that the nature of subordination relations between them also affects the legal nature of the legal acts issued by them and the requirements imposed on them. The main goal of improving subordinate lawmaking is the creation and functioning of a unified, internally consistent, consistent system of legal norms. The main content of the article is to disclose the content of the concept of “legal monitoring” in relation to the law-making of executive authorities of different levels. The legal regulation of one of its most important tools, the analysis of regulatory impact, is critically investigated. The authors propose to introduce into the law-making terminology the categories “legal requirements for management acts” and “subjects of law formation” as components of the lawmaking process of executive authorities. This may become a new stage in the study of lawmaking processes, and also contributes to the emergence of new approaches to the study of the phenomenon of law education. The novelty of these approaches is due to the emergence of new regulatory instruments in the practice of domestic legal education that meet the needs of the lawmaking mechanism of modern Kazakhstan. This will allow us to reach a new level of lawmaking support for state policy, increase the level of legal culture and, in general, the rule of law.